Metropolitan areas in central Poland and their impact on migration flows - Michal Bernard Pietrzak; Justyna Wilk (Institute of Economic Research (IER), 2014)
The objective of the paper is to identify subregions (NUTS 3) of the central part of Poland pretending to metropolitan areas, as well as to study their impact on the domestic migration flows. Their social and economic situations in 2008 were determined on the basis of the composite measure values. Their participation in the domestic migration flows in the period 2008-2010, considering the directions, range and intensity of flows, was also examined. Only Warsaw is the completely shaped metropolitan area in Poland. The city demonstrates the highest economic potential and therefore the strongest migration flows and dependences with other subregions. The cities of Poznan and Lodz and also the Bydgosko-Torunski subregion can be recognized as developing metropolitan areas. These subregions represent significant economic centres; however migration flows related to them demonstrate mainly regional importance.
Keywords: J11; O11; R11; R23; 330; metropolitan areas; migration flows; economic development; central Poland